MÁS ALLÁ DE LA ESTÉTICA: JORGE EDUARDO EIELSON FRENTE AL LEGADO PREHISPÁNICO - Cavagnaro Farfán, Franco (2017)
Through a journey of his essays and his own literary work, this article analyzes and establishes the basic context that pushed Jorge Eduardo Eielson to understand the pre-Hispanic legacy. For this purpose, it presents the heritage’s legal aspects and his poetic intuition through the ideas of other writers and artists. This conscience acts in counterpoint to the position taken by Jorge Eduardo Eielson in the 1980s in favor of a curatorial position vis-à-vis heritage assets. In addition, the article makes the artist’s understanding of the Pre-Hispanic past evident. Through a multidisciplinary approach, the Andean iconography and architecture about which the poet wrote about in his essay is analyzed. In such a way, the article establishes the intuition that Jorge Eduardo Eielson had developed from his exile, as an inversion of Italian monumentality and which is recreated in the poetry he wrote in that country. That is, through his approach to the Pre-Hispanic past, unknown and/or unappreciated, during his life in Lima, the artist puts forward a spectacular revaluation from exile.